KEWENANGAN PEMERINTAH DAERAH TERHADAP HAK PENGUASAAN ATAS TANAH - Urip Santoso (Faculty of Law, Universitas Jenderal Soedirman, 2012)
Tenure of land that can be controlled by local government is the right to use and the right to managing the Land. The authority of local government to the land which has the status of right to use by using the land for the benefit of its duties. If the land has the right to managing statutes, the authority is planning the design and the use of land, using the land for the benefit of its duties, and handed the right of managing land to the third parties and/or work with the third parties. Local government are not authorized to lease the right of land and the right of management to another party. Keywords: authority, local government, tenure of land